PROCESSING HOUSE HOLD POLYETHYLENE WASTE TO PRODUCE CARBON NANOTUBES - Smagulova G.T.; Peter J.F. Harris; Mansurov Z.A. (Academic Scientific Journal of Chemistry, 2019)
The paper presents the results of processing household polyethylene waste by thermal degradation for the synthesis of carbon nanotubes by chemical vapor deposition. A feature of the work is that the decomposition of polyethylene samples and the synthesis of carbon nanotubes were carried out in one stage. The effect of temperature on the decomposition products of polyethylene wastes in the temperature range 200-550 ° C was investigated. It has been determined that even at a temperature of 450 ° C, the decomposition of polyethylene proceeds sufficiently to form carbon nanotubes. The catalyst for the growth of CNTs was cenospheres obtained from the ash and slag waste of thermal power plants during coal combustion. The main components of cenospheres are silicon and aluminum oxides. The active phase of the catalyst was iron nitrate, which is a precursor to the formation of iron clusters on the surface of cenospheres. The decomposition of polyethylene waste and the synthesis of carbon nanotubes was carried out one-stage in a tubular CVD reactor in a nitrogen atmosphere. The temperature of the synthesis of CNTs is 800 ° C. As a result of synthesis, carbon nanotubes with a diameter of 15-28 nm are formed on the surface of cenospheres, which is confirmed by results of SEM analysis and Raman spectroscopy. Based on the studies, the authors proposed a method for processing polyethylene waste for the synthesis of high quality CNTs